Characteristics of joint involvement and relationships with systemic inflammation in systemic sclerosis : results from the EULAR Scleroderma Trial and Research Group (EUSTAR) database - Avouac. J. (Array, 2010)
Objective was To determine the prevalence of and independent factors associated with joint involvement in a large population of patients with systemic sclerosis (SSc). This study was cross-sectional, based on data collected on patients included in the European League Against Rheumatism (EULAR) Scleroderma Trials and Research (EUSTAR) registry. We queried this database to extract data regarding global evaluation of patients with SSc and the presence of any clinical articular involvement: synovitis (tender and swollen joints), tendon friction rubs (rubbing sensation detected as the tendon was moved), and joint contracture (stiffness of the joints that decreased their range of motion). Overall joint involvement was defined by the occurrence of synovitis and/or joint contracture and/or tendon friction rubs. We recruited 7286 patients with SSc ; their mean age was 56 +/- 14 years, disease duration 10 +/- 9 years, and 4210 (58%) had a limited cutaneous disease subset. Frequencies of synovitis, tendon friction rubs, and joint contractures were 16%, 11%, and 31%, respectively. Synovitis, tendon friction rubs, and joint contracture were more prevalent in patients with the diffuse cutaneous subset and were associated together and with severe vascular, muscular, renal, and interstitial lung involvement. Moreover, synovitis had the highest strength of association with elevated acute-phase reactants taken as the dependent variable. Our results highlight the striking level of articular involvement in SSc, as evaluated by systematic examination in a large cohort of patients with SSc. Our data also show that synovitis, joint contracture, and tendon friction rubs are associated with a more severe disease and with systemic inflammation.